PHYLLODY (FLOWER ABNORMALITY) IN SWEET CHERRY (PRUNUS AVIUM L.) - H. Engin; Z. Gokbayrak (Journal of Animal and Plant Sciences, 2010)
This report deals with a case of phyllody, flower abnormality which is described as leaf-like development of the floral organs. In most extreme form, the organ involved is replaced by a foliage-type leaf. Any floral organ, even the ovule, may become leafy in form or color.
Keywords: NA